2022
DOI: 10.1002/jmri.28538
|View full text |Cite
|
Sign up to set email alerts
|

Peritumoral and Intratumoral Texture Features Based on Multiparametric MRI and Multiple Machine Learning Methods to Preoperatively Evaluate the Pathological Outcomes of Pancreatic Cancer

Abstract: Background: Radiomics-based preoperative evaluation of lymph node metastasis (LNM) and histological grade (HG) might facilitate the decision-making for pancreatic cancer and further efforts are needed to develop effective models. Purpose: To develop multiparametric MRI (MP-MRI)-based radiomics models to evaluate LNM and HG. Study Type: Retrospective. Population: The pancreatic cancer patients from the main center (n = 126) were assigned to the training and validation sets at a 4:1 ratio. The patients from the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 38 publications
0
3
0
Order By: Relevance
“…Intratumoral and peritumoral CT Radiomics enhances the predictive performance in estimating complete pathological response after neoadjuvant chemoradiation in patients with esophageal squamous cell carcinoma with an AUC of 0.852 (95% CI, 0.753–0.951) [ 35 ]. Radiomics based on peritumoral and intratumoral MRI demonstrates an AUC of 0.924 − 0.875 when evaluating lymph node metastasis (LNM) in pancreatic cancer, and an AUC of 0.944 − 0.892 for assessing histological grade [ 36 ]. Perilesional radiomics features improved the discrimination ability of the radiomics signature in diagnosing prostate cancer [ 37 ].…”
Section: Discussionmentioning
confidence: 99%
“…Intratumoral and peritumoral CT Radiomics enhances the predictive performance in estimating complete pathological response after neoadjuvant chemoradiation in patients with esophageal squamous cell carcinoma with an AUC of 0.852 (95% CI, 0.753–0.951) [ 35 ]. Radiomics based on peritumoral and intratumoral MRI demonstrates an AUC of 0.924 − 0.875 when evaluating lymph node metastasis (LNM) in pancreatic cancer, and an AUC of 0.944 − 0.892 for assessing histological grade [ 36 ]. Perilesional radiomics features improved the discrimination ability of the radiomics signature in diagnosing prostate cancer [ 37 ].…”
Section: Discussionmentioning
confidence: 99%
“…Correspondingly, previous studies have demonstrated the significant predictive capabilities of peritumoral radiomics models about pathological outcomes, lymph node metastasis, and recurrence risk stratification. These findings suggest that the peritumoral region of various tumors, including intrahepatic cholangiocarcinoma, cervical cancer, and breast cancer, may contain additional valuable predictive and diagnostic information (60)(61)(62). However, the efficacy of EUS-based peritumoral radiomics methodologies in facilitating the differentiation between NF-PNETs and insulinomas remains uncertain.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the NCCN guideline recommends serial CT with contrast for routine follow-up to determine therapeutic benefit. There have been some investigations using MRI based, or PET-CT based radiomics to predict histological grade and survival in PDAC ( 32 , 33 ). MRI has good soft tissue resolution, and Xie et al.…”
Section: Discussionmentioning
confidence: 99%
“…MRI has good soft tissue resolution, and Xie et al. showed that MRI-based radiomics holds the potential to evaluate histological grade of PDAC with AUC values of 0.944 and 0.892 in the validation and external test sets ( 32 ). However, this preference for using MDCT as the main imaging tool in many hospitals and imaging centers is mainly due to the higher cost and lack of widespread availability of MRI compared to CT. Xing et al.…”
Section: Discussionmentioning
confidence: 99%